CEREBELLAR LIPONEUROCYTOMA IN THE LAST DECADE: A COMPREHENSIVE CASE REVIEW - Oskar Sienkiel; Julia Czerwik; Marcin Narloch; Jan Tomczyk; Mateusz Jasiński; Aleksandra Żywicka; Michał Szalach; Kamila Mozga; Mathias Spitaleri; Dawid Sewruk; Karol Kanon (International Journal of Innovative Technologies in Social Science, 2025)
Introduction. Tumors of the central nervous system (CNS) are relatively uncommon when compared with neoplasms arising in other organs and tissues of the human body. Among these rare entities, cerebellar liponeurocytoma represents one of the least frequently encountered tumor types. This neoplasm was originally described in 1978 by Bechtel and colleagues, who referred to it as a “mixed mesenchymal and neuroectodermal tumor” due to its unusual histological characteristics combining neuronal and lipomatous differentiation. Since that time, only a limited number of cases have been reported in the literature, underlining its exceptional rarity. In subsequent decades, advances in neuropathology and molecular diagnostics have allowed for more precise recognition of this lesion as a distinct clinicopathological entity. Within the World Health Organization (WHO) classification of tumors of the central nervous system published in 2016, cerebellar liponeurocytoma was formally designated as a grade II tumor. This reflects its generally indolent biological behavior but also acknowledges the significant potential for local recurrence following treatment. Aim of the Study. The aim of the study was to collect data about symptoms and immunoreactivity of cerebellar liponeurocytoma from published cases between 2014 and 2024. Materials and Methods. PubMed and Scopus databases were used to search for cerebellar liponeurocytoma cases. Result. Analyzing data from 32 cases of cerebellar liponeurocytoma, 11 men (34.4%) and 21 women (65.6%) were affected. The mean age was 42.9 ± 18.17 years. The youngest person was 6 years old and the oldest was 77. Two cases concerned patients under 18 years old. The most common tumor location was the posterior fossa (25/32 cases, 78.12%), followed by the ventricle area (4 cases, 12.5%) and the frontal lobe (1 case). The most common symptoms were headache (26/32, 81.25%), vomiting and nausea (15/32, 46.9%), gait disturbance (14/32, 44%), ataxia (3/32, 9.4%), paresthesia (3/32, 9.4%), and urge incontinence (1 case). Conclusion. Cerebellar liponeurocytoma is a rare but distinctive tumor of the central nervous system. The usual symptoms arise from the tumor’s typical location in the cerebellum. Its clinical course, with atypical features, may pose significant management challenges. Further research into the tumor’s molecular and genetic characteristics is needed to provide insights into optimizing management strategies and improving patient outcomes.